Anak Yatim dan Wali: Sebuah Riset Atas Pengelolaan Harta Anak Yatim di Gampong Mongeudong dalam Perspektif Hukum Islam dan UU Perkawinan - Munawar Khalil; Chaliddin Chaliddin (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2023)
Children are an important part of the younger generation who play a strategic role in shaping better families. Therefore, children need adequate guidance and protection to ensure their physical, psychological, mental, and social growth and development. This research discusses the management of orphaned children's assets in Gampong Mongeudong and the review of Islamic law and the Marriage Law on the management of orphaned children's assets. The research method used is field research conducted in the real life of the community. The results of the research show that the management of orphaned children's assets is done by family members, including fathers, mothers, grandmothers, or uncles. However, the process of determining the guardian of orphaned children does not comply with the provisions of the law. From the perspective of Islamic law, the maintenance of orphaned children's assets should be carried out by the guardian who is the closest relative in the line of guardianship. However, this guardianship must comply with several provisions, including the prohibition for the guardian to mix their assets with the assets of the child under their guardianship, the prohibition to excessively consume the child's assets, and the obligation to return the child's assets when the child reaches adulthood.